Assessing the impacts of internal communication: Employer branding and human resources - Raquel Fernandes; Bruno Sousa; Manuel Fonseca; José Castro Oliveira (Administrative Sciences, 2023)
Human capital is considered the most important resource in any organization. However, most companies are concerned with external customer satisfaction, without devoting much attention to the satisfaction of their employees. Indisputably, employee satisfaction is fundamental and determines the success or failure of what the customer experiences. Technological developments have changed our lives and habits, and even the way we relate to others, so the online increasingly influences the offline. The purpose of this manuscript was to examine the relationship between the Digital Communication of companies and their Employer Branding, with a special focus on the close relationship that employees feel with the company. To perform this analysis, a case study was carried out using a qualitative approach. Interviews with seven managers from three different companies, two of whom are responsible for the Digital Communication of their organizations, were performed. With the analysis of the data obtained, it is concluded that the Employer Branding perceived by the employees is of a positive image of the company, but they do not feel emotionally more connected with the organization through the Digital Communication practiced by it. With this study, it is expected that organizations recognize the importance that an online presence has in the image of their brand as a whole, and that it is important to invest in Digital Communication, but it has to be performed with an action plan to achieve the objectives intended. From an interdisciplinary perspective, the manuscript presents insights for marketing (digital marketing and employer branding) and for socially responsible behavior by organizations (in a Portuguese context).
Keywords: 350; digital communication; employer branding; social media; social responsibility